Nursing Care for Adult Patients in critical condition from Acute Respiratory Distress Syndrome (ARDS) and Acute Kidney Injury (AKI) receiving Continuous renal replacement therapy (CRRT): Critical Nurse' s Roles and Nephrology Nurse's Roles - Yodpanya, Supattra; Chompooin, Decha; Klinnak, Warin (Journal of health and health management, 2025)
The study of patient care concepts for those with acute respiratory distress syndrome (ARDS) and acute kidney injury (AKI) has shown that placing the patient in a prone position helps improve gas exchange and oxygenation. The use of muscle relaxants allows the patient to breathe in sync with the ventilator, while appropriate ventilator settings help reduce the risk of complications associated with mechanical ventilation.Dialysis treatment with continuous renal replacement therapy (CRRT) plays a crucial role in removing excess fluid and waste from the body, maintaining water and electrolyte balance, and correcting acidosis. Therefore, I have studied case management concepts and outcomes to develop a care approach that facilitates patient recovery from a critical state. This is presented in the form of a case study based on standard professional nursing practice.This approach enhances nurses’ understanding of the roles of both critical care nurses and dialysis nurses, ensuring they have the knowledge and expertise needed to care for patients with ARDS and AKI undergoing CRRT while preventing complications. In the critical care unit, nurses can effectively manage patients with unstable blood pressure during dialysis by closely monitoring vital signs and observing the patient’s condition to ensure safety throughout the critical phase.